THE RELATIONSHIP BETWEEN METALINGUISTIC AWARENESS AND THE DELETION OF FINAL /R/ IN WORDS IN THE WRITING OF CHILDREN FROM BAHIA IN THE LITERACY IN A (POST) PANDEMIC CONTEXT - de Freitas, Amanda Cristina (2024)
Metalinguistic Awareness (MA) has been found important for acquiring writing skills (Barrera; Maluf, 2003). The /R/ deletion in speech is also found in writing, as noted by Dutra and Pinto (2014) and Santos and Costa (2013). This study investigates the relationship between MA and /R/ deletion in the writing of children in the process of literacy acquisition. The study included 58 students from 1st to 3rd grades in a private and a public school in Feira de Santana, Bahia. Children in higher grades demonstrated better writing skills and less deletion of /R/. Contexts of resyllabification in oral language did not affect the realization of final /R/. A moderate to strong correlation was found between the CM index obtained and the tasks involving writing and dictation of words ending in /R/. The pandemic context may have also influenced the children's performance.